Ligand Engineering Achieves Suppression of Temperature Quenching in Pure Green Perovskite Nanocrystals for Efficient and Thermostable Electroluminescence - Chen, Kaiwang; Du, Qing; Cao, Qiufen; Du, Chao; Feng, Shangwei; Pan, Yutong; Liang, Yue; Wang, Lei; Chen, Jiangshan; Ma, Dongge (Nano-Micro Letters, 2024)
Formamidinium lead bromide (FAPbBr3) perovskite nanocrystals (NCs) are promising for display and lighting due to their ultra-pure green emission. However, the thermal quenching will exacerbate their performance degradation in practical applications, which is a common issue for halide perovskites. Here, we reported the heat-resistant FAPbBr3 NCs prepared by a ligand-engineered room-temperature synthesis strategy. An aromatic amine, specifically β-phenylethylamine (PEA) or 3-fluorophenylethylamine (3-F-PEA), was incoporated as the short-chain ligand to expedite the crystallization rate and control the size distribution of FAPbBr3 NCs. Employing this ligand engineering approach, we synthesized high quality FAPbBr3 NCs with uniform grain size and reduced long-chain alkyl ligands, resulting in substantially suppressed thermal quenching and enhanced carrier transportation in the perovskite NCs films. Most notably, more than 90% of the room temperature PL intensity in the 3-F-PEA modified FAPbBr3 NCs film was preserved at 380 K. Consequently, we fabricated ultra-pure green EL devices with a room temperature external quantum efficiency (EQE) as high as 21.9% at the luminance of above 1,000 cd m−2, and demonstrated less than 10% loss in EQE at 343 K. This study introduces a novel room temperature method to synthesize efficient FAPbBr3 NCs with exceptional thermal stability, paving the way for advanced optoelectronic device applications. Highlights: 1 The innovative synthesis of pure green FAPbBr3 nanocrystals at room temperature was exploited by employing aromatic amine ligands to refine the perovskite nanocrystals with high quality and excellent optoelectronic properties. 2 The proposed ligand engineering strategy firstly realized the suppression of emission thermal quenching effect in the organic-inorganic hybrid FAPbBr3 nanocrystals. 3 It was demonstrated that the FAPbBr3 based light-emitting diodes achieved a room temperature external quantum efficiency (EQE) of 21.9% at the luminance of 1580 cd m-2, and only presented less than 10% loss in EQE at a higher temperature of 343 K.